2006
DOI: 10.1002/pmic.200600290
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the E2F1 response in p53-negative cancer cells: New aspects in the regulation of cell survival and death

Abstract: E2F1 is an essential transcription factor that regulates cell-cycle progression and apoptosis. Overexpression of E2F1 sensitizes neoplastic cells to apoptosis and leads to tumor growth suppression, making it an interesting target for anticancer therapy. Use of E2F1 as a therapeutic, however, requires a detailed knowledge of the mechanisms by which it controls cellular proliferation and apoptosis, and of other potential E2F1 activities. In this study, a differential proteome analysis was performed to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 52 publications
1
26
0
2
Order By: Relevance
“…In addition, we have identified two DNA sequences resembling E2F binding sites, one located in close proximity (partially overlapping) to the distal GC-box (Ϫ324 to Ϫ311) and a second in the ERSE 1 element (Ϫ126 to Ϫ108) as part of the GC-rich motif. Saos-2 cells that stably express the ER-E2F1 fusion protein were used to conditionally regulate E2F1 activation through 4-OHT administration (25,30). After synchronization of cells by serum starvation, nuclear translocation of E2F1 was induced by the addition of 1 M 4-OHT for 24 h. DNA-protein complexes were immunoprecipitated with antibodies against E2F1 and IgG.…”
Section: E2f1 Binds the Grp78/bip Promoter In Vivo And Abolishesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have identified two DNA sequences resembling E2F binding sites, one located in close proximity (partially overlapping) to the distal GC-box (Ϫ324 to Ϫ311) and a second in the ERSE 1 element (Ϫ126 to Ϫ108) as part of the GC-rich motif. Saos-2 cells that stably express the ER-E2F1 fusion protein were used to conditionally regulate E2F1 activation through 4-OHT administration (25,30). After synchronization of cells by serum starvation, nuclear translocation of E2F1 was induced by the addition of 1 M 4-OHT for 24 h. DNA-protein complexes were immunoprecipitated with antibodies against E2F1 and IgG.…”
Section: E2f1 Binds the Grp78/bip Promoter In Vivo And Abolishesmentioning
confidence: 99%
“…Previously, we performed a differential proteomic analysis to identify proteins associated with E2F1 activity in inducible p53-deficient cells (25). This approach revealed that E2F1 decreases the protein level of GRP78/BIP.…”
mentioning
confidence: 99%
“…Li et al used a proteomic analysis approach to understand the role of E2F1 in p53-negative tumor cells [27]. E2F1 is a transcription factor that plays an important role in cell-cycle progression and apoptosis.…”
Section: The Current State Of Osteosarcoma Proteomicsmentioning
confidence: 99%
“…This construction permitted conditional activation of E2F1 after addition of 4-hydroxytamoxifen (4-OHT) to the cultures (Stanelle et al 2002). 2-DE analysis of E2F1 induced and non-induced Saos-2 cells' proteome led to the identification of 33 novel differentially regulated E2F1 target proteins by MALDI-MS (Li et al 2006b), 15 upregulated and 18 dowregulated. Only eight of these differentially regulated proteins harbor E2F-consensus sites in their promoter (Rabinovich et al 2008): SRSF1, TUBB, GDI2, H2B.1, TCP1γ, HNRNPA2/B1, HNRNPK and MATR3.…”
Section: Protein Profiling To Elucidate E2f Functionmentioning
confidence: 99%
“…Functional analysis of E2F1-regulated target genes suggests that E2F1 plays predominantly a negative role in Saos-2 cellular proliferation. By altering the balance between anti-and pro-apoptotic Bcl-2 family members, E2F1 would render cells susceptible to both mitochondrial apoptosis and ER-stress related death signals (Li et al 2006b). These results are consistent with the findings described by several groups, including ours, in mouse models lacking E2F1, and favor the hypothesis that E2F1 plays anti-proliferative and pro-apoptotic roles in vivo (Field et al 1996;Garcia et al 2000;Yamasaki et al 1996).…”
Section: Protein Profiling To Elucidate E2f Functionmentioning
confidence: 99%